THE IMPACTS OF UNITED STATES EMBARGO ON VENEZUELA DURING PRESIDENT NICOLÁS MADURO’S ADMINISTRATION - Nuranilam, Nuranilam; Prawira, Muhammad Rizky; Khaldun, Riady Ibnu (Department of International Relations Universitas Satya Negara Indonesia, 2025)
This research analyzes the impact of U.S. embargo on Venezuela’s struggling economy, worsened by falling global oil prices. Venezuela relies heavily on oil exports, and the decline in oil prices has led to a significant drop in revenue. During Venezuelan President Nicolás Maduro’s administration, U.S. sanctions—such as restrictions on international finance, a ban on oil trade, and asset freezes—have intensified the crisis. The study uses a qualitative descriptive methodology and case study approach, relying on secondary data and literature reviews. Findings show that U.S. sanctions have worsened Venezuela’s economic situation, leading to hyperinflation, shortages of essential goods, and reduced foreign investment. The oil sector, crucial for national revenue, has seen declines in production and exports, exacerbating the budget deficit. Additionally, the sanctions have triggered a humanitarian crisis, increased poverty, and caused mass migration. This study emphasizes that U.S. sanctions disrupt economic stability and severely affect citizens’ daily lives, creating a destructive cycle that further deteriorates Venezuela’s economic, social, and humanitarian conditions.